PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Endah Prihartini; Eli Achmad Mahiri; Mira Juliastri (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
Work productivity is one of the keys to achieving company goals. But in reality, there are still some employees who have not shown their work productivity optimally. This phenomenon also occurs at PDAM Tirta Bhakti Raharja Majalengka, where there is a mismatch between the target and the realization achieved by employees. Productive employees are able to encourage companies to meet targets, so work productivity greatly affects company performance. This research uses descriptive and verification analysis methods. One of them is by distributing questionnaires to obtain data. The population in this study were 56 employees of the central office of PDAM Tirta Bhakti Raharja Majalengka Regency. The sampling technique is saturated sampling technique. The research instrument test used is validity and reliability test. The data analysis used includes multiple linear regression analysis, classical assumption test and coefficient of determination test, hypothesis testing with the support of SPSS 26. The results obtained from this study indicate that the work environment does not have a significant effect on employee performance. Meanwhile, work productivity is influenced by the incentives provided.